KEGIATAN MEDIA TRIP MANCANEGARA OLEH BAGIAN PUBLIKASI MANCANEGARA KEMENTERIAN PARIWISATA - Yanti Setianti; Heru Ryanto Budiana; Oklitha Arifah (Prodi Ilmu Komunikasi, FISIP, Universitas Muhammadiyah Cirebon, 2020)
Media Trip Mancanegara is a media relations activity by Director for International Publication due to the lowest news coverage about Indonesian tourism destinations on the foreign media. The target of Media Trip Mancanegara is foreign media who has etchic code, news segmentation, news standard and policy linked to their native country. The research aims to know the planning of Media Trip Mancanegara, communication and action of Media Trip Mancanegara by Director for International Publication. The methodology used is qualitative with descriptive study. The result of the research is the planning of Media Trip Mancanegara started with problem mapping, aim and principle of Media Trip Mancanegara, also deciding foreign media, place and date of Media Trip Mancanegara and making the itinerary. Communication with the foreign media was 2 weeks before the Media Trip Mancanegara. Media Trip Mancanegara held at 10th-13th September 2018 and visited Londa, Ke’te Kesu’, Rambu Solo and media session with North Toraja Tourism Office. One of the attraction failed to watch because of the miscommunication between Director for International Publication and tour guide. Keywords : media relations, media trip mancanegara, tourism ministry.